2013
DOI: 10.14233/ajchem.2013.14731
|View full text |Cite
|
Sign up to set email alerts
|

in vitro Antioxidant Activity and Total Phenolic Content of Various Extracts of Satureja hortensis L. Collected from Turkey

Abstract: The antioxidant capacities of the acetone, ethanol and water extracts of leaves and flowers of S. hortensis were estimated using different antioxidant tests, including lipid peroxidation, reducing power, 1,1-diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging, iron chelation, superoxide anion radical scavenging and hydrogen peroxide scavenging. The contents of antioxidant components in these extracts were also determined. Results showed that the highest contents of these components including phenols and flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Other phytochemical investigations have shown that the aboveground parts of such representatives of the Lamiaceae family as Mentha, Melissa, Salvia, Origanum, Hyssopus, Ocimum, Satureja and Dracocephalum are rich in phenolic compounds with pronounced antioxidant properties [3,6,7,9,14]. For example, Gougoulias and Mashev [3] on studying seven plants from Greek and Bulgaria revealed that infusions obtained from Origanum vulgare herb had the highest amount of total phenols (13.55 mg GAE/g dw).…”
Section: Current Issues In Pharmacy and Medical Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other phytochemical investigations have shown that the aboveground parts of such representatives of the Lamiaceae family as Mentha, Melissa, Salvia, Origanum, Hyssopus, Ocimum, Satureja and Dracocephalum are rich in phenolic compounds with pronounced antioxidant properties [3,6,7,9,14]. For example, Gougoulias and Mashev [3] on studying seven plants from Greek and Bulgaria revealed that infusions obtained from Origanum vulgare herb had the highest amount of total phenols (13.55 mg GAE/g dw).…”
Section: Current Issues In Pharmacy and Medical Sciencesmentioning
confidence: 99%
“…Many researchers have used different organic solvents to extract phenolic compounds from plant material [9,13,14]. A few publications are, hence, dedicated to the phenolic…”
Section: Introductionmentioning
confidence: 99%
“…antinociceptive and anti-inflammatory (Hajhashemi et al 2002); antibacterial (Dincer et al 2013); antioxidant (Yesiloglu et al 2013) leaves antimicrobial (Rota et al 2004);antibacterial (Nedorostova et al 2011;Sfeir et al 2013); cytotoxic, antioxidant, and antimicrobial (Miladi et al 2013); antioxidant and antimicrobial (Cavar et al 2008) leaves and flowered aerial part 42 Scutellaria baicalensis antioxidant and antiinflamatory (Seok et al 2016); cardiovascular, kidney, and liver diseases (Lai et al 2016) leaves 43 Scutellaria indica L. antitumour (Min et al 1997); antioxidant (Kim et al 2009) leaves 44 Sideritis scardica Griseb.…”
Section: Medicinal Plants Of the Family Lamiaceaementioning
confidence: 99%
“…Altundag and Aslim (2011), Baser et al (2001), Yucel et al (2009) , Eminagaoglu et al (2007), Kosar et al (2003Kosar et al ( , 2008, Kulisic et al (2005), Oke et al (2009aOke et al ( , 2009b Alinkina et al (2013), Alizadeh (2011), Alizadeh et al (2010a), Bandoniene et al (2002), Deighton et al (1994), Dikbas et al (2011), , Esquivel et al (1999), Exarchou et al (2002), Gulluce et al (2003), Hosseini et al (2013), Inotai et al (2012), Kalantzakis and Blekas (2006), Kosar et al (2005), Madsen et al (1996Madsen et al ( , 1998, Plander et al (2012), Shojaee-Aliabadi et al (2013), Trojakova et al (2001), and Yesiloglu et al (2013) …”
Section: S Wiedemannianamentioning
confidence: 99%